Ascorbic acid co-administered with rosuvastatin reduces reproductive impairment in the male offspring from male rats exposed to the statin at pre-puberty - Leite, Gabriel Adan Araújo [UNESP]; Figueiredo, Thamiris Moreira [UNESP]; Guerra, Marina Trevizan [UNESP]; Borges, Cibele dos Santos [UNESP]; Fernandes, Fábio Henrique [UNESP]; Anselmo-Franci, Janete Aparecida; Kempinas, Wilma De Grava [UNESP] (Elsevier, 2018)
Obesity during childhood and adolescence is closely related to dysfunctions on lipid profile in children. Rosuvastatin is a statin that decreases serum total cholesterol. Ascorbic acid is an important antioxidant compound for male reproduction. Pre-pubertal male rats were distributed into six experimental groups that received saline solution 0.9% (vehicle), 3 or 10 mg/kg/day of rosuvastatin, 150 mg/day of ascorbic acid, or 3 or 10 mg/kg/day of rosuvastatin co-administered with 150 mg/day of ascorbic acid by gavage from post-natal day (PND)23 until PND53. Rats were maintained until adulthood and mated with nulliparous females to obtain the male offspring, whose animals were evaluated at adulthood in relation to reproductive parameters. This study is a follow up of a previous paper addressing potential effects on F0 generation only (Leite et al., 2017). Male offspring from rosuvastatin-exposed groups showed increased sperm DNA fragmentation, androgen depletion and impairment on the testicular and epididymal structure. Ascorbic acid coadministered to the fathers ameliorated the reproductive damage in the offspring. In summary, paternal exposure to rosuvastatin may affect the reproduction in the male offspring; however, paternal supplementation with ascorbic acid was able to reduce the reproductive impairment in the male offspring caused by statin treatment to the fathers.
Keywords: Male offspring; Reproduction; Statin; Toxicology; Vitamin C